2015
DOI: 10.4049/jimmunol.1402342
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Receptor for Advanced Glycation End Products Exacerbates Lymphoproliferative Syndrome and Lupus Nephritis in B6-MRL Fas lpr/j Mice

Abstract: The receptor for advanced glycation end products (RAGE) is a pattern recognition receptor that interacts with advanced glycation end products, but also with C3a, CpG DNA oligonucleotides, and alarmin molecules such as HMGB1 to initiate a proinflammatory reaction. Systemic lupus erythematosus is an autoimmune disorder associated with the accumulation of RAGE ligands. We generated mice invalidated for RAGE in the lupus-prone B6-MRL Fas lpr/j background to determine the role of RAGE in the pathogenesis of systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…Next, to examine the activation status of the CD4 + and CD8 + T cells, we determined the early activation marker CD69 expression. Activated CD69 + CD4 + T cells were increased in Fas lpr/lpr mice as previously reported [36], but SH3BP2 de ciency signi cantly suppressed the activation of CD4 + T cells in the spleen (Fig. 3c).…”
Section: Sh3bp2 De Ciency Blunts the Aberrant Accumulation Of Cd3 + Bsupporting
confidence: 86%
“…Next, to examine the activation status of the CD4 + and CD8 + T cells, we determined the early activation marker CD69 expression. Activated CD69 + CD4 + T cells were increased in Fas lpr/lpr mice as previously reported [36], but SH3BP2 de ciency signi cantly suppressed the activation of CD4 + T cells in the spleen (Fig. 3c).…”
Section: Sh3bp2 De Ciency Blunts the Aberrant Accumulation Of Cd3 + Bsupporting
confidence: 86%
“…However, as discussed, in the context of murine models of SLE, TLR9 deficiency exacerbates disease outcome. Remarkably, RAGE-deficient B6/lpr mice also develop more severe nephritis (77). Whether FasL-induced HMGB1, under the appropriate conditions, can also contribute to a TLR9-mediated negative feedback loop is yet one more question that can be addressed in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…These studies suggested that RAGE reduces the accumulation of autoreactive CD3(+)B220(+)CD4(−)CD8(−) T lymphocytes, and that deletion of Ager exacerbates lymphoproliferative syndrome, autoimmunity, and organ injury. From the studies, we may infer that RAGE is able to rescue apoptosis of T lymphocytes when Fas/CD95 is not present or functional [67]. …”
Section: 0 Rage and Roles In Autoimmunity And Chronic Inflammationmentioning
confidence: 99%